(untitled) (Islamic Sciences Journal, 2023)
The fundamentalists were keen to set controls and restrictions to allow interpretation, to preserve the provisions of this religion, as saying interpretation and opening its doors without restrictions and conditions leads to the spread of corruption and deviation, and disruption in the legal rulings, so here are the misguided sects that have been corrupted only as a result of excessive interpretation, at the same time. Closing the door of interpretation and acting on the apparent meaning of the texts also obstructs the rulings and distances itself from the spirit of legislation. The reason for choosing this topic is: 1- What the issue of interpretation is of great importance in understanding the requirements and meanings contained in the legal texts, whether in the wise book or in the purified Sunnah. 2 What the interpretation leads to in terms of the vast assimilation of the perceptions and the rich implications contained in these texts. 3- The reality of the shining miracle that is evident in the texts of the Great Qur’an. The research was divided into four chapters as follows: The first chapter: The concept of interpretation, its conditions and types according to the fundamentalists, and it contains three topics: The first topic: the concept of interpretation The second topic: the conditions of interpretation, and there are two requirements. The first requirement: interpretation of language and law The second requirement: the difference between interpretation and interpretation The third topic: Types of interpretation Chapter Two: Jurisprudential Applications to Interpretation of the Fundamentalists in the Chapter on Worship, and it contains two topics: The first topic: the menstruating woman touching the Qur’an The second topic: Paying the value instead of the eye in zakat Chapter Three: Jurisprudential Applications to Interpretation of the Fundamentalists in the Chapter of Transactions, which includes two topics The first topic: the choice of the council. The second topic: the guarantee of the stolen. Chapter Four: Jurisprudential Applications to Interpretation of the Fundamentalists in the Chapter of Penalties,